The gender equality policies in times of crisis. The Galician case - Diz, Isabel; Lois, Marta (Investigaciones Feministas (Feminist Research), 2015)
This article focus on the development and recent transformations of gender public policies in Galicia. The main aim is to test the influence of the current financial-economic crisis as well as the changes of political color of the party in government produced in the last years. In order to attain this general aim we are going to answer the following questions: Which type of equality political actions have been carried out by the governments of Xunta de Galicia? Has the development of these policies involved some change since 2010? Has the development of this policies been influenced by the political color of the government? Do resources matter? And finally, is gender mainstreaming institutionalized?
Keywords: Welfare; Equality; Gender Policies; Social Cost